Product design and development - Ulrich, Karl T.; Eppinger, Steven D. 1961- (Irwin McGraw-Hill, 2008)
This text presents a set of product development techniques aimed at bringing together the marketing, design, and manufacturing functions of the enterprise. The integrative methods facilitate problem-solving and decision-making.
Keywords: Industrial engineering; Industrial management; New products -- Management; Production management; Produktgestaltung; Produktentwicklung; Industriedesign; Lehrbuch